Promising Thermoelectric Performance in Two-Dimensional Semiconducting Boron Monolayer - Hu, Yonglan; Li, Ding; Liu, Rongkun; Li, Shichang; Feng, Chunbao; Li, Dengfeng; Ding, Guangqian (Frontiers in Chemistry, 2021)
Heavy element is a special character for high thermoelectric performance since it generally guarantees a low lattice thermal conductivity. Here, we unexpectedly found promising thermoelectric performance in a two-dimensional semiconducting monolayer consisting of light boron element. Using first-principles combined with Boltzmann transport theory, we shown that in contrast to graphene or black phosphorus, the boron monolayer has a low lattice thermal conductivity arising from its complex crystal of hexagonal vacancies. The conduction band with intrinsic camelback shape leads to the high DOS and high n-type Seebeck coefficient, while the highly degenerate valence band along with the small hole effective mass contribute to the high p-type power factor. As a result, we obtained the p-type thermoelectric figure of merit up to 0.96 at 300K, indicating that boron monolayer is a promising p-type thermoelectric material.